Nepotism and Its Social Impact on Life in Hadith Perspective - isna, isnayanti; Gaffar, Abdul (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2024)
Nepotism is one of the social disease phenomena that has existed since ancient times and still exists today. This article aims to discuss Nepotism and its impact on social life from the perspective of the hadith of the Prophet PBUH. In addition, data was also obtained from other related documents such as books and relevant research. The results of this study show that nepotism is the practice of giving certain positions, beliefs or tasks to others, both family and close friends, without considering their credibility and capabilities where things are not based on their ability to carry out tasks or positions, but because of personal relationships. As a result, this can trigger chaos and even destruction within the organization or institution in question. Some of the characteristics of the practice of nepotism are depicted in the hadith of the Prophet, such as the absence or even lack of professionalism and expertise in the tasks given, as well as the absence of integrity, namely the inability to realize his ideas and thoughts for the sake of the public interest. Therefore, this can trigger chaos in the pattern of social comfort and even result in the destruction of the hereafter.